HAVE DIGITAL MEDIA PLATFORMS A ROLE IN FOSTERING A POLARIZED PUBLIC DEBATE? EVIDENCES FROM LATIN AMERICA - Paroni, Bruna; Marino, Giada; Giglietto, Fabio; Choucair, Tariq; O’Connor Farfan, Kate; Svegaard, Sebastian; Bruns, Axel; Bonow Soares, Felipe; Osborne-Carey, Cassian; Tavares, Camilla Quesada (AoIR Selected Papers of Internet Research, 2026)
In recent years, democracies worldwide have experienced a sharp rise in political polarization, coinciding with the global spread of digital media platforms (Yarchi et al., 2021). After the Pink Tide in Latin America, which brought left-wing leaders to power following years of autocratic rule, the past decade has seen a resurgence of a new conservative right, leading to protests and the rise of illiberal populism. Over the past two years, several Latin American countries have seen an uprising of extreme right-wing political actors and parties. The region’s conservative agenda often relies on leader personalization to legitimize political and social issues (Rennó, 2022). In Argentina, Javier Milei’s 2023 rise exemplifies this rhetoric. In Brazil, despite Lula Da Silva’s moderate government, extreme right-wing sentiments persist, evident in the January 8 Brasília attacks and recent results of local elections. As Chile approaches its 2025 elections, the impact of digital media on politics remains crucial. This phenomenon is not limited to Latin America (Chaguri & Amaral, 2023); Donald Trump’s re-election in the U.S. highlights the global link between social media and political polarization, underscoring the need for international attention. Although research on political polarization is growing, it remains relatively new in Latin America (Bello, 2023) compared to the US, where most studies are concentrated (Marino & Iannelli, 2023). While polarization is not inherently a threat to democracy, destructive political polarization (Esau et al., 2024) can severely harm democratic processes. In such cases, hybrid media ecosystems and their sociotechnical features contribute to the decline of public spheres (Casal Bértoa & Rama, 2021). The studies in this panel explore how social media platforms drive polarization by analyzing platform affordances, user behavior, and the textual elements shaping public debate. Through diverse methodological approaches, the panel offers insights into key issues across Latin American case studies and various social media platforms. Choucair and colleagues introduce a novel method to identify "otherness" in political speeches by Brazil, Mexico, Colombia, Argentina, and Peru leaders. By analyzing target identities ("whom") alongside issues, ideologies, partisan choices ("what"), and sentiments and interactions ("how"), the study shows how targets are demonized and vilified as enemies. This approach advances polarization studies by revealing the targets of polarized rhetoric and enhancing our understanding of how discursive strategies shape in-group and out-group perceptions in Latin America. Soares and Osborne-Carey analyze the discourse of pro-Bolsonaro supporters on Facebook during the 2022 Brazilian elections, highlighting how political narratives contributed to the January 8th, 2023 insurrection in Brasília. The study challenges a narrow binary definition of disinformation, showing that supporters framed their actions as defending and ’restoring’ democracy, claiming it was lost with Lula’s return. These findings underscore the need to consider such imaginaries when studying political disinformation and the limitations of rigid ’right’ vs. ’wrong’ information dichotomies. Tavares examines online comments directed at Brazilian federal congresswomen after the "Rape PEC" (PEC 164/12) proposal to ban legal abortion. Analyzing Instagram comments, the study explores how political alignment shapes discourse and polarization. Right-wing politicians supported the PEC using religious values, while left-wing politicians emphasized women’s rights. Social media dynamics and online communities contributed to commenters aligning with posts and exchanging attacks, intensifying the polarized debate. Paroni, Marino, and Giglietto analyze how politicians’ visual communication on Instagram influenced destructive polarization during the 2024 São Paulo local elections. The study examines allegations that a mayoral candidate boosted his campaign by paying for viral short videos, leading to high engagement, an imbalanced election environment, and attacks on the opposition. The research underscores the impact of visual media on digital interactions and democratic processes, highlighting the growing role of image-based strategies in political campaigns. The panel will contribute to the scholarly discourse on political polarization by providing empirical insights and theoretical perspectives with regional and global relevance.